Analysis of the role of internal audit with the quality of financial reports at pt bank sulselbar - ANDI ANDHY MUHAMMAD MUBARA (International Journal of Multidisciplinary Research and Studies, 2023)
This research aims to examine the relationship between internal audit functions and the quality of financial reports at PT Bank Sulselbar. The study took place at PT Bank Sulselbar and utilized a quantitative research approach. The sample was determined using a survey technique that included all members of the population, totaling 30 individuals. The primary data was collected through the distribution of questionnaires. Regression Analysis was employed as the statistical method to test the hypotheses. The results indicated a significant correlation between the internal audit role and the quality of financial reports at PT Bank Sulselbar. These findings have positive implications, suggesting that PT Bank Sulselbar should continue enhancing the quality of its financial statement preparation and presentation.